Needs analysis-based ESP course design for vocational high school students - Abdul Kamaruddin; Nurul Fitria; Andi Patmasari (Universitas Muhammadiyah Malang, 2021)
The objectives of this research were to find out: (1) the needs of accounting students in learning English at one of the vocational high schools in Donggala; and (2) the suitable English course design for vocational high school students. This research used a descriptive qualitative research method by involving twenty-two students majoring in accounting. The research instruments were google form questionnaires and phone interview that each instrument contained open-ended and close-ended questions. The data of this research were analyzed in four stages; namely coding, data reduction, data display, and drawing conclusions or interpretations. The researchers found that the needs of accounting students who participated in the research in learning English were in accordance with the teaching concepts of English for Specific Purposes. The language skill they needed the most was speaking. The students lacked vocabulary, pronunciation, and self-confidence to speak in English. In line with the students’ lack, the students would like their speaking skill to be developed. Based on the result of the students’ needs analysis, the researchers suggested a set of English course guidelines which consisted of four components. The first was the course rationale that covered target learners, course content, and course objectives. The second component was course materials related to accounting and about daily life. The third was teaching method and learning activities that most of the students preferred discussions and practices. The last component was assessment which consisted of a portfolio, journal, interview, observation, and self/peer assessment. The teacher could use one assessment only or more in one time for assessment based on the learning situation and the students’ needs.